The Role of Islamic Finance In Economic Development - Khodijah Ishak (LPPM ISNJ Bengkalis, 2018)
This paper aims to determine Islamic finance refers to investments that are permissible in accordance with Sharia, Islamic law. Sharia law views money as a measuring tool for value and not an “asset” itself. “It does not permit receipt and payment of riba(interest), gharar (excessive uncertainty), maysir (gambling), short sales or financing activities that it considers harmful to society” (IMF website). The paper relies on functions, and variance decomposition analysis, focusing on the period from January 1994 to May 2007. The results show that both Islamic banks’ financing and deposit play important roles in the monetary transmission process in the Malaysian economy. In particular, both Islamic deposit and financing are shown to be statistically significant in linking the monetary policy indicator to the real output. The results imply that the monetary authority should also consider the Islamic banks in the implementation of monetary policy in Malaysia. The results also imply that ensuring the stability of the Islamic financial institutions is just as important as that of the conventional counterpart to achieve an effective transmission of monetary policy in the economy. This paper is a pioneer study undertaking the empirical investigation on the role of Islamic banks in the monetary transmission process in an economy.